Keeping millennials from quitting due to work stress: The roles of mattering, commitment and entrepreneurship orientation - Kususanto Ditto Prihadi; Calvin K.W. Chang; Lyann Goo (Intelektual Pustaka Media Utama, 2021)
Studies in pre-pandemic era had established that millennial workers tend to leave their job due to low organizational commitment or strong entrepreneurial orientation; however, the pandemic had brought down economy due to lockdowns, work stress and mental health instability, limitation of business hours, working from home policy, downsizing of companies, and many other changes. This situation might contribute to a novel situation among millennial employees and their turnover intention might be developed differently. Because mattering has protective feature against work stress and depression, we hypothesized that their it will negatively contribute to their turnover intention, and this contribution is mediated by the organizational commitment. Furthermore, we also hypothesized that this phenomenon would only occur in the condition of lower levels of entrepreneurial orientation. Data was collected from 354 purposively recruited millennial employees who responded to the scales of mattering, organizational commitment, entrepreneurial orientation and turnover intention through online surveys Analyses were conducted with Bootstrap Method in PROCESS Macro Model 10. The findings indicated that the moderated mediation occurred; organizational commitment fully mediated the link between mattering and turnover intention among participants with moderate and high levels of entrepreneurial orientation.